"We Are Our Own Counselor": Resilience, Risk Behaviors, and Mental Health Service Utilization among Young African American Men. Issue 3 (1st October 2020) - Bauer, Alexandria G.; Christensen, Kelsey; Bowe-Thompson, Carole; Lister, Sheila; Aduloju-Ajijola, Natasha; Berkley-Patton, Jannette
Abstract: Despite risk for trauma, subsequent mental health concerns, and poor health outcomes, young Black/African American men (YBM) are less likely to receive mental health services than other racial/ethnic groups. Despite the growing literature on resilience, there is less information on relationships between resilience, risk behaviors, and use of mental health services. This study sought to examine resilience, trauma-related risk behaviors, and receipt of mental health services among a sample of YBM who experienced trauma. Focus groups and a brief survey were conducted with YBM ( N = 55) who had been exposed to at least one traumatic event (e.g., witnessing violence, experienced serious injury or illness) and were recruited from urban community settings (e.g., colleges/universities, barbershops, churches). Participants were an average age of 23 years (SD = 3.9; range 18–30) and experienced an average of 2 to 3 traumatic events (SD = 2.2). Trauma exposure was a significant predictor of risk factors ( β = .513, p < .01). However, resilience did not significantly moderate this relationship. Resilience also did not predict receipt of mental health services. Culturally relevant qualitative themes found to be related to resilience included maintaining resilience autonomously, preferred coping methods (e.g., friends, music), and habituating to adversity. This study has potential to inform the development of culturally tailored, relevant interventions to promote engagement in mental health services among YBM who've experienced trauma.